TINJAUAN AKSELERASI TRANSFORMASI DIGITAL PT BANK MANDIRI (PERSERO) TBK - Samsiah (2021)
Entering the economic 4.0, digital transformation acceleration is one of the most important agenda in industry life in Indonesia, including in the banking industry. Many processes and work activities that were originally carried out conventionally must be radically changed to ensure that the company can adapt and be able to face increasingly strong competitors. For this reason, bankers, whether bank employees or customers concerned with finances institutions, must prepare themselves to face technological changes to a more modern direction. The banking industry must have an innovative strategy to develop digital transactions so that it has a big impact for the company. However, the existence of digital transformation will directly affect banking performance, be it profits or losses. Therefore, banks must also be prepared to face the risks that will occur in the future and develop strategies to overcome these risks. Banks must also prepare a digital roadmap so that the implementation of banking digital transformation can be carried out properly and in a structured manner.